Square Roots in Vedic Mathematics - Parajuli, Krishna Kanta (Mathematics Education Forum Chitwan, 2019)
This paper specially concentrates on finding the square roots of perfect as well as imperfect square numbers by the Vedic sutra Vilokanam. Generally, extracting the square root of a number is considered a tedious job. There are two methods taught in our present-day classroom by conventional approach to find square roots, which are lengthy and time consuming. But, the Vedic Sutra Vilokanam helps us to find square root of such numbers with a little practice. The technique mentioned for extracting square root for imperfect square numbers does not belong solely to Vedic Mathematics written by Swami Bharati Krishna Tirthaji Maharaja. Mathematicians have been using it as a part of their general practice. However, the technique for calculating square roots and described in Vedic Mathematics is difficult. The methods discussed and organization of the content of the paper here are intended to show the Vedic Mathematics as an extremely refined and efficient mathematical system than conventional system.